Substantiation of conditions of effective working capacity of tribocouples of the details made of polymeric composite materials with high-modulus fillers - Aulin, V.V.; Hrynkiv, A.V.; Ly, S.V.; Livitskyi, O.M. (Problems of Tribology, 2022)
This work is devoted to the study of the conditions of effective performance of triad couplings of parts made of polymeric composite materials. The stress state of the material is associated with the characteristics of the accumulation of dislocations, the energy of activation of their movement. The average stress, friction stress is determined. Based on this, expressions for estimating critical stresses and loads on tribocouple parts are obtained. The distribution of the force on the tribocoupling of parts is determined taking into account the quality characteristics of the friction surfaces, modulus of elasticity and Poisson's constant of the components of the polymer composite material. This problem is considered for tribocouples of parts of various kinds. Expressions for calculation of nominal pressures at different types of contact of material of details of tribocoupling are received, and also the equations on which it is possible to estimate in them values of nominal critical pressure are resulted. The conditions for efficient operation of tribocoupling of parts made of polymer composite materials are clarified. It is determined that a significant increase in the nominal critical pressure on the tribocoupling is possible with the use of high-modulus fillers, the modulus of elasticity of which is greater than the modulus of elasticity of the polymer matrix